História e cultura afro-brasileiro em Sergipe : antecedentes da Lei 10639/03 - (1980-2003) - Bispo, Denise Maria de Souza (2015)
This study has the objective to objective to show up the research about the experiences that discuss the History and Afro-Brazilian Culture in Sergipe in the periods between 1980 and 2003. The research was drawn from the analysis of the legislative sources produced in universities, in entities and individuals involved in dealing with related matters, somehow, racism and prejudice that contributed to outline the Law 10.639, approved nationally on 09 january 2003. In Sergipe context, there are institutions and entities, with proposals toenhance the african-brazilian culture in different spaces and spheres, from cultural representations till the incetive to deploy n the educational sphere History linked to black population. Therefore, the invisibility of some of these actions motivated the development of this research that show subject in relation to racial issues in the three decades noticed. In this process we have seen advances, setbacks and we can see three movements guided to racial issues in Sergipe: the first, a movement that is before the post-military dictatorship where one begins to inquiry the position of blacks in society and expose the inherited ills by the black population in the post-abolition. The second (moviment), which is structured paths to recognition of blacks in law defense grounds, such as the joints in the legislature. And the last movement is organized to build structures that would ensure the execution of rights and an amplitude in their actions. These three movements make up the History of racial issues Sergipe and build agendas and positions that were reflected in Sergipe black movements.